TECHNIQUES FOR SENTINEL LYMPH NODE BIOPSY IN BREAST CANCER PATIENTS - Zdravkovic, Darko (Medical Research, 2025)
Breast cancer is the most frequent cancer among woman worldwide. Primary, cancer cells spread through the lymph vessels. One of the most accurate prognostic factors in breast cancer patients is the status of the axillary lymph nodes. Axillary lymph node staging in breast cancer patients was initially performed by axillary lymph node dissection. Sentinel lymph node biopsy is the standard of care in clinically and radiologically negative axilla. According to current guidelines double contrast is recommended procedure in terms of identification od the sentinel lymph node. Nowadays, there are several new tracers in clinical practice with high identification rate and low false negative results.There are no facilities for the application of the new and radioactive tracers in many medical centars worldwide due to technological and matherial reasons. The application of blue dye alone is reliable and effective diagnostic and surgical procedure with high identification rate and low false negative results.